2019
DOI: 10.1103/physrevmaterials.3.053402
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic insulating ground state in transition metal dichalcogenide TiSe2

Abstract: The transition metal dichalcogenide TiSe2 has received significant research attention over the past four decades. Different studies have presented ways to suppress the 200 K charge density wave transition, vary low temperature resistivity by several orders of magnitude, and stabilize magnetism or superconductivity. Here we give the results of a new synthesis technique whereby samples were grown in a high pressure environment with up to 180 bar of argon gas. Above 100 K, properties are nearly unchanged from pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…[16] it was shown that the resistivity of TiTe 2 followed the Bloch-Grüneisen (B-G) formulation for scattering due to electron-phonon coupling. We therefore adopt this form of scattering rate for our model of TiSe 2 : the coefficient of the B-G scattering term is a free parameter which we set for good agreement on the absolute value of resistivity around ρ peak , and the Debye temperature of the B-G term is set to 250 K [2,14]. We also add a constant scattering term from elastic impurity scattering, which is set such that ρ exp T →0 = m * e /N e |e| 2 τ 0 .…”
Section: Simulation Of Resistivitymentioning
confidence: 99%
See 4 more Smart Citations
“…[16] it was shown that the resistivity of TiTe 2 followed the Bloch-Grüneisen (B-G) formulation for scattering due to electron-phonon coupling. We therefore adopt this form of scattering rate for our model of TiSe 2 : the coefficient of the B-G scattering term is a free parameter which we set for good agreement on the absolute value of resistivity around ρ peak , and the Debye temperature of the B-G term is set to 250 K [2,14]. We also add a constant scattering term from elastic impurity scattering, which is set such that ρ exp T →0 = m * e /N e |e| 2 τ 0 .…”
Section: Simulation Of Resistivitymentioning
confidence: 99%
“…extrinsic electron doping) reported by Di Salvo et al [1] [23]. Campbell et al [14] recently argued against any link between the height of the peak and the sample stoichiometry. However, our simulations are in line with the earlier intuition that the two are indeed related [1,3,5].…”
Section: Variation With Net Carrier Densitymentioning
confidence: 99%
See 3 more Smart Citations